1989
DOI: 10.2118/17161-pa
|View full text |Cite
|
Sign up to set email alerts
|

Solids-Free Brine-in-Oil Emulsions for Well Completion

Abstract: Summary. An invert emulsion fluid composed of brine (e.g., NaCl, NaBr, CaCl2, CaBr2, and ZnBr2) emulsified into hydrocarbon oil (e.g., diesel, crude, or mineral) was formulated with a mixture of nonionic surfactant emulsifiers. Laboratory investigations were conducted to define the emulsion characteristics and to develop methods for controlling the fluid's rheological properties and emulsion stability at elevated temperatures. This system has oil as the external phase, and the stability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Brine-in-oil emulsions have been previously proposed and reported as having been used as packer fluids 11 . In this paper, we present the development of an oil-based gravel pack carrier fluid.…”
Section: Spe 64978mentioning
confidence: 99%
“…Brine-in-oil emulsions have been previously proposed and reported as having been used as packer fluids 11 . In this paper, we present the development of an oil-based gravel pack carrier fluid.…”
Section: Spe 64978mentioning
confidence: 99%
“…In their study, three emulsifiers were required to provide a stable emulsion. Ezzat and Blatell (1989) documented formulations at 40/60 to 50/50 OWR. However these utilized zinc bromide and a polymerized surfactant that necessitated use at higher concentrations when the brine or water phase increased to 60 vol%.…”
Section: Introductionmentioning
confidence: 99%
“…Nicora et al (2001) reported a more traditional oil/water range of 65/35 to 85/15 as this ratio in the field is often dictated by the concentration of solids from weighting agents, clay and formation which can reach 35 to 40 vol% of total solids. At this concentration, Nicora et al reported unacceptable rheology. In spite of many attempts to develop high internal phase ratio (HIPR) OBMs for OWRs (20/80 to 50/50) with higher water content in the internal phase, the use or success has been very limited (Daynes et al 1987;Ezzat and Blatell 1989;Nicora et al 2001). The primary focus in the development of invert systems has been on the choices of external phase, internal phase, weight materials and other solids content (Nicora et al 2001) while maintaining the drilling performance characteristics expected with OBM.…”
Section: Introductionmentioning
confidence: 99%